Biodiversity and Carbon Storage in Mangroves with Varying Protection in North Sulawesi - Wawan Nurmawan; Martina A. Langi (Jurnal Penelitian Pendidikan IPA, 2025)
Mangrove ecosystems contribute to biodiversity conservation and climate-change mitigation through carbon storage. This study assessed the association between biodiversity (flora and fauna) and carbon stocks in mangroves of North Sulawesi across three management contexts: a conservation zone (Bunaken), a protected forest (Sondaken), and an unprotected area (Bitung). Field surveys were conducted to compile species inventories, and carbon stocks were estimated from biomass measurements. Protected sites showed higher species richness and larger carbon stocks than the unprotected site. Species richness was positively and significantly correlated with carbon storage, indicating that sites with greater biodiversity also tended to store more carbon. These results support the role of effective protection in maintaining both ecological integrity and carbon sequestration capacity. In conclusion, strengthening mangrove protection in North Sulawesi is likely to deliver co-benefits for biodiversity conservation and climate mitigation.